Sotagliflozin in Patients with Diabetes and Chronic Kidney Disease - Szarek M; Pitt B; Cannon CP; Leiter LA; McGuire DK; Lewis JB; Riddle MC; Inzucchi SE; Kosiborod MN; Cherney DZI; Dwyer JP; Bhatt DL; et al. (Massachusetts Medical Society, 2021)
BACKGROUND The efficacy and safety of sodium–glucose cotransporter 2 inhibitors such as sotagliflozin in preventing cardiovascular events in patients with diabetes with chronic kidney disease with or without albuminuria have not been well studied. METHODS We conducted a multicenter, double-blind trial in which patients with type 2 diabetes mellitus (glycated hemoglobin level, ≥7%), chronic kidney disease (estimated glomerular filtration rate, 25 to 60 ml per minute per 1.73 m2 of body-surface area), and risks for cardiovascular disease were randomly assigned in a 1:1 ratio to receive sotagliflozin or placebo. The primary end point was changed during the trial to the composite of the total number of deaths from cardiovascular causes, hospitalizations for heart failure, and urgent visits for heart failure. The trial ended early owing to loss of funding. RESULTS Of 19,188 patients screened, 10,584 were enrolled, with 5292 assigned to the sotagliflozin group and 5292 assigned to the placebo group, and followed for a median of 16 months. The rate of primary end-point events was 5.6 events per 100 patient-years in the sotagliflozin group and 7.5 events per 100 patient-years in the placebo group (hazard ratio, 0.74; 95% confidence interval [CI], 0.63 to 0.88; P<0.001). The rate of deaths from cardiovascular causes per 100 patient-years was 2.2 with sotagliflozin and 2.4 with placebo (hazard ratio, 0.90; 95% CI, 0.73 to 1.12; P=0.35). For the original coprimary end point of the first occurrence of death from cardiovascular causes, nonfatal myocardial infarction, or nonfatal stroke, the hazard ratio was 0.84 (95% CI, 0.72 to 0.99); for the original coprimary end point of the first occurrence of death from cardiovascular causes or hospitalization for heart failure, the hazard ratio was 0.77 (95% CI, 0.66 to 0.91). Diarrhea, genital mycotic infections, volume depletion, and diabetic ketoacidosis were more common with sotagliflozin than with placebo. CONCLUSIONS In patients with diabetes and chronic kidney disease, with or without albuminuria, sotagliflozin resulted in a lower risk of the composite of deaths from cardiovascular causes, hospitalizations for heart failure, and urgent visits for heart failure than placebo but was associated with adverse events.